The Potential Assesment of Communities for Eco – tourism and Cultural tourism Development, Case Study of Ban tha – Long Community , Ubon Ratchathani Province and Ban tha – Wat Community , Sakon Nakhon Province. - Juansan , Passakorn (Journal for Developing the Social and Community, 2022)
The purposes of this study were : 1) to study potential of the communities for improving to Eco-tourism and Cultural-tourism. 2) to obtain data for processing and developing to Eco-tourism and Cultural-tourism. This research worked in 2 study areas ; 1) Ban Tha Long, Huay Phai Sub District, Khong Chiam District, Ubon Ratchathani Province. 2) Ban Tha Wat, Lao Po Dang Sub District, Muang District, Sakon Nakhon Province. Research method was worked by questionnaire survey from selected household and interviewed with community leaders, Government officer who involve in the study area, the local shop entrepreneurs, homestay services and local people. The finding showed that both communities, Ban Tha Long and Ban Tha Wat, have an average ( ) at a high level in ecotourism and percentage tally (%) for cultural tourism is high level as well. The conclusion pointed out that both communities have the potential to be Eco-tourism and Cultural-tourism nevertheless there are the factors should be improved are encouraged the local people do more participate in tourism activities and suggested to the Government entire local and national level plan to develop the tourist attractions accordingly and explicitly. There are two development approaches: community level development should encourage people The private sector and community leaders are involved in decision making. Open a public forum for the community to determine the direction of the area's development There are government agencies to support in planning in terms of mapping, potential and linking with other tourist attractions and the proactive work of government and regional levels. Regional development there should be a study and promotion of tourism that is linked as a tourism route by using the connection point in the dimension of cultural tourism with a story or way of life along the Mekong in order to create a tourist destination in the region